(untitled) (Damascus University Journal of agriculture sciences, 2024)
The research was conducted at a private poultry house in Homs between 10 August, 2020 and 10 January, 2022. A total of 412-one day old chicks of an egg laying hybrid (Hy-Line), producing white shell eggs, raised from one day old until 74 weeks of age: chicks were randomly distributed into four groups with three replicates of 35 birds per each. All groups were under the natural decreased day light during rearing phase except first week, at the nineteenth week different lighting regimes were applied (during production phase), The first group (control) was subjected to an increased lighting system, the second group was subjected to an intermittent lighting system so that the period of darkness between two periods of illumination was two hours, the third group was subjected to an intermittent lighting system so that the period of darkness between two periods of illumination was three hours, the fourth group was subjected to an intermittent lighting system so that the period of darkness between two periods of illumination was four hours, the following productive parameters were studied for each replicate: the percentage of unsittable eggs, egg weight, egg density, shell thickness, shell relative weight, albumen index, albumen relative weight, yolk index, yolk relative weight, white to yolk ratio, haugh units and yolk color degree. Results showed that using intermittent lighting during production period had improved the average egg weight, whereas it had not significantly affected. the parameters for Table egg quality, the percentage of unstable eggs, compared to an increased lighting system.